THE RITUAL COMMUNICATION AS A MEDIUM FOR CULTURAL PRESERVATION AND COLLECTIVE IDENTITY: Study on Nyadran Sonoageng Tradition - Siti Noer Tyas Tuti; Reza Safitri (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
Nyadran Sonoageng tradition is a Javanese ritual that combines spiritual values, local culture and Islamic teachings. This study uses a sociocultural approach with communication ethnography method to explore the Nyadran tradition in maintaining social harmony in the midst of changing times. Based on James W. Carey's ritual communication perspective, this study found that symbolic elements such as jolen offerings, processions, and kenduri act as a medium of symbolic communication capable of transmitting collective values. Cross-generational participation in this ritual shows that Nyadran's role as a space to build communication harmony and maintain cultural continuity in a society. The transformation of implementation from simple or traditional to modernization in the implementation of Nyadran, such as the integration of entertainment elements and folk markets, shows the flexibility of tradition in responding to the dynamics of modernization.